2013
DOI: 10.7717/peerj.173
|View full text |Cite
|
Sign up to set email alerts
|

Why do leaf-tying caterpillars abandon their leaf ties?

Abstract: Leaf-tying caterpillars act as ecosystem engineers by building shelters between overlapping leaves, which are inhabited by other arthropods. Leaf-tiers have been observed to leave their ties and create new shelters (and thus additional microhabitats), but the ecological factors affecting shelter fidelity are poorly known. For this study, we explored the effects of resource limitation and occupant density on shelter fidelity and assessed the consequences of shelter abandonment. We first quantified the area of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…Importantly, caterpillars abandon their shelters long before the resource is exhausted: the damage per shelter that was left by a caterpillar was on average 21% of the area of leaves from which it was composed. This result is in line with findings by Sliwinski and Sigmon (2013) who observed similar behaviour in two other species of leaf-tying caterpillars and concluded that the abandonment of shelters by solitary caterpillars can be driven by factors other than a lack of food. Plant defences are known to force herbivores to leave their feeding sites, leading to dispersion of damage within a plant (Edwards & Wratten, 1983).…”
Section: Behaviour Of Caterpillars Of Carpatolechia Proximellasupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, caterpillars abandon their shelters long before the resource is exhausted: the damage per shelter that was left by a caterpillar was on average 21% of the area of leaves from which it was composed. This result is in line with findings by Sliwinski and Sigmon (2013) who observed similar behaviour in two other species of leaf-tying caterpillars and concluded that the abandonment of shelters by solitary caterpillars can be driven by factors other than a lack of food. Plant defences are known to force herbivores to leave their feeding sites, leading to dispersion of damage within a plant (Edwards & Wratten, 1983).…”
Section: Behaviour Of Caterpillars Of Carpatolechia Proximellasupporting
confidence: 92%
“…In line with this hypothesis, we suggest that abandonment of shelters by leaf‐tiers well before the resources are exhausted is an adaptation that decreases the risk of parasitism. However, long trips in search of a site suitable for shelter construction, which may take as long as an half an hour (Sliwinski & Sigmon, , and our observations), are associated with an increased risk of mortality from visually oriented predators (Bergelson & Lawton, ; Loader & Damman, ) and other risks. For example, dropping from a plant during travel caused 17% mortality in two Psilocorsis species (Sliwinski & Sigmon, ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…2), whose continued presence often had to be assessed using feeding damage or changes to the shelter structure, rather than direct observation of the caterpillar. The disappearance of some caterpillars may also be more complicated than simple predation, as caterpillars can fall from their plants while seeking new shelter sites (Loeffler, 1996; Sliwinski & Sigmon, 2013). Although these caterpillars are not removed from the plant by predators, they can be killed by terrestrial predators before they can return to the plant (Sliwinski & Sigmon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The disappearance of some caterpillars may also be more complicated than simple predation, as caterpillars can fall from their plants while seeking new shelter sites (Loeffler, 1996; Sliwinski & Sigmon, 2013). Although these caterpillars are not removed from the plant by predators, they can be killed by terrestrial predators before they can return to the plant (Sliwinski & Sigmon, 2013). Despite these complications, shelter‐building caterpillars offer an excellent opportunity to directly measure predation in the field.…”
Section: Discussionmentioning
confidence: 99%